Agricultural residue valorization using a hydrothermal process for second generation bioethanol and oligosaccharides production. (September 2015) - Vargas, Fátima; Domínguez, Elena; Vila, Carlos; Rodríguez, Alejandro; Garrote, Gil
Highlights: An environmentally friendly process for barley straw valorization has been developed. High amounts of xylooligomers have been obtained. Fed batch simultaneous saccharification and fermentation was optimized. 52 g ethanol/L was obtained working at high solids loading (4 g liquid/g solid). Abstract: In the present work, the hydrothermal valorization of an abundant agricultural residue has been studied in order to look for high added value applications by means of hydrothermal pretreatment followed by fed-batch simultaneous saccharification and fermentation, to obtain oligomers and sugars from autohydrolysis liquors and bioethanol from the solid phase. Non-isothermal autohydrolysis was applied to barley straw, leading to a solid phase with about a 90% of glucan and lignin and a liquid phase with up to 168 g kg −1 raw material valuable hemicellulose-derived compounds. The solid phase showed a high enzymatic susceptibility (up to 95%). It was employed in the optimization study of the fed-batch simultaneous saccharification and fermentation, carried out at high solids loading, led up to 52 g ethanol/L (6.5% v/v).